Activity as resource among pensioners in modern society - Johnsen, Hanne Cecilie; Andresen, Kari Grande; Evensen †, Aud Emelie; Brataas, Hildfrid Vikkelsmo (Nordisk Tidsskrift for Helseforskning, 2023)
Background: Society is changing, and there is a need for more knowledge about how traditional leisure activities and activities facilitated in the modern society are used by today’s pensioners, and the significance of activities for the experience of health, quality of life, and meaning in life. Method: Qualitative descriptive method with conventional data analysis of students’ written reports on individual interviews with old-age pensioners. Results: Two topics emerged; activity, and health and quality of life. The pensioners combined traditional activity and activities facilitated in modern society. They were both performers and enjoyers in activities organized in the society. Some traditional activities seem to disappear. Health and quality of life encompassed staying in shape, sense of coherence and well-being. Conclusion: Traditionality and modernity seem to coexist in the pensioners’ choice of activity. Activity appears as a salutogen health resource. More knowledge about how activities is offered to the eldest generation needed.
Keywords: activity; elderly; health; quality of life; modernity; pensioner